Kimči - Urbanc, Mimi (Geografski obzornik, 2003)
Kimchi is the general term given to a group of fermented vegetable food that has been an elementary food in Korea for ages. It has been traditionally served as a "must" at almost every meal, even breakfast, along with soup, stew, pancakes, boiled rice, and the other dishes as well lately with pasta and pizza, the favourite food of the youth. With Korea taking part in the process of international integration, kimchi has been successfully introduced to the globalized modern world. It has gained popularity especially in Japan and the United States of America.
Keywords: Koreja; prehrana; food; zelenjava; začimbe; dišavnice; kimči; uporaba; priprava